(untitled) (Costos y Gestión, 2020)
In this research, an Activity Based Budgeting procedure is designed, which helps to improve cost information as a basis for analysis and control for decision making. It starts from a study on the budgeted costs in the Food and Beverage process in Cuban hotels that operate under the «All Inclusive» modality, taking as an example the Brisas Santa Lucia Hotel. The proposed procedure enriches the cost analysis by comparing it with Activity Based Costing that is performed with the same level of detail of the information to strengthen cost control through the basis of the causes of the deviations detected as a starting point for management decision making. The present work has been carried out with the intention of providing a tool for entrepreneurs in the hotel sector to improve the budgeting process in the Food and Beverage process, contributing to the management of their costs. The proposed procedure may be generalized in entities with similar characteristics.